Negative for AL and ATTR: Could It Still Be Amyloid? - Ahmed B. Elawad; Paul Wilkinson; Ryan Kimball; Ahmed F. Abdulrahim (Annals of Internal Medicine: Clinical Cases)
Amyloidosis is a systemic disease characterized by the extracellular deposition of misfolded proteins. We present a rare case of familial amyloidosis with multiorgan involvement. A 68-year-old woman initially presented with shortness of breath and syncope. Past medical history included chronic kidney disease, skin bronzing, and macroglossia. An echocardiogram revealed asymmetric septal hypertrophy, which prompted serum marker testing for common forms of amyloidosis. These tests returned negative for light-chain and transthyretin amyloidosis. Later genetic testing confirmed an APOA1 gene mutation. This case highlights the importance of considering hereditary forms of amyloidosis, particularly when tests for light-chain and transthyretin amyloidosis are negative.